计算:((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)的 值

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/01 23:04:40
计算:((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)的 值
xjA_% Yfv6B}ȜfFE6/lm"%U:U^mR`9gFzvt;'Sq07TOcq1prջ_eYG\(`]2  u}>u/ҏv|%Ԃ奂}GQܼ e^,Dvw:eBiGetFw㚉ja`iJ8bJ!e3 zBxf`{:Et3F("դs,j*yŴ(ca8ԥurN/r\( JcZm˨79*I TAQ&OKRYANMʐCx_Q\ڳ|HZ$j3nSFӴy.Əz뎈̘,23kflHUң`C׷$~s

计算:((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)的 值
计算:((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)的 值

计算:((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)的 值
过程详见下图:

((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)
=[a/(a+b)+b/(a-b)-2ab/(a+b)(a-b)]÷(b-a)/ab
={[a(a-b)+b(a+b)-2ab]/(a+b)(a-B)}*ab/(b-a)
=[(a^2+b^2-2ab)/(a+b)(a-b)]*ab/(b-a)
=-[(a-b)^2/(a+b)(a-...

全部展开

((a/a+b)-(b/b-a)-(2ab/a平方-b平方)除以(1/a-1/b)
=[a/(a+b)+b/(a-b)-2ab/(a+b)(a-b)]÷(b-a)/ab
={[a(a-b)+b(a+b)-2ab]/(a+b)(a-B)}*ab/(b-a)
=[(a^2+b^2-2ab)/(a+b)(a-b)]*ab/(b-a)
=-[(a-b)^2/(a+b)(a-b)]*ab/(a-b)
=-ab/(a+b)

收起

还有半边括号放在哪里啊?